2003
DOI: 10.1063/1.1530583
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excitation of out-of-plane vibrations and vibrational energy redistribution after internal conversion of 4-nitroaniline

Abstract: Articles you may be interested inHigh resolution IR diode laser study of collisional energy transfer between highly vibrationally excited monofluorobenzene and CO2: The effect of donor fluorination on strong collision energy transfer Theoretical investigation of highly excited vibrational states in DFCO: Calculation of the out-of-plane bending states and simulation of the intramolecular vibrational energy redistribution Mode dependent intracluster vibrational energy redistribution rate in size-selected benzoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…No evidence for conformational or other inhomogeneous broadening in PNA in DMSO, a polar solvent, emerged, in alignment with RREP analysis. [17] Qualitative and quantitative aspects of the vibrational dynamics confirm the reports of Werncke et al [28,29] However, a careful evaluation of the details of the evolution shows some interesting, and previously unreported, mode-specific vibrational decay rate constants. Little effect of l EX on these lifetimes was discovered.…”
supporting
confidence: 75%
See 4 more Smart Citations
“…No evidence for conformational or other inhomogeneous broadening in PNA in DMSO, a polar solvent, emerged, in alignment with RREP analysis. [17] Qualitative and quantitative aspects of the vibrational dynamics confirm the reports of Werncke et al [28,29] However, a careful evaluation of the details of the evolution shows some interesting, and previously unreported, mode-specific vibrational decay rate constants. Little effect of l EX on these lifetimes was discovered.…”
supporting
confidence: 75%
“…[28,29] These authors showed that PNA behaves in a manner contrary to the interpretation of rapid thermalization and vibrational cooling proposed by Ernsting et al [24][25][26] The findings support the important role of out-of-plane NO 2 motion in IC, and show nonthermal vibrational energy distributions, particularly among the higher frequency modes, persisting for 6-7 ps. The kinetics of both IVR and VR were slower in TRARRS experiments than in the less direct TRA studies.…”
mentioning
confidence: 54%
See 3 more Smart Citations